Optimalisasi Penggunaan, Pemanfaatan, Pemindahtanganan, Pemusnahan, dan Penghapusan Barang Milik Daerah - Rakhmansyah, Mohamad; Susanto, Sugeng; Ikraman, Ikraman; Sunarya, Po Abas (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
The purpose of this research is to minimize potential losses and ensure that the rental process of assets owned by the South Tangerang City Government is carried out efficiently and in accordance with applicable regulations by identifying potential risks that may arise in the process of renting local assets, such as the risk of damage to goods, legal non-compliance, or financial risk. The methodology used in the study of risk profiles and risk management patterns in projects utilizes the COSO method in this case, activities such as Focus Group Discussions (FGD) and field surveys are conducted for verification Stakeholders involved in the FGD activities include Government Agencies, Businesses, Academics, and Practitioners. The risk of renting local government property has important implications for the local government Some of the implications that may arise, as well as recommendations for managing these risks, include risk implications and risk management recommendations Taking the risk of renting local government property seriously and implementing these recommendations can help the local government manage risks better and maintain stability and reputation in rental operations.